FAKTOR RISIKO OPERASI BERULANG PASCA ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION - Luh Putu Surya Sintia Dewi; Anak Agung Gede Eka Septian Utama (Kinetic and Physiotherapy Comprehensive, 2023)
Background: ACL reconstruction (ACLR) is a surgical procedure to graft the ACL using tendon tissue to restore joint fixation and stabilization functions. Rehabilitation management is performed by physiotherapy in ACLR phase III patients to increase strength, balance, and functional motion control of patients with rehabilitation and exercise adaptation interventions. Case Description: On June 09, 2022, the patient was playing basketball, when the patient heard his leg "pop" due to sudden stopping and turning movements while playing basketball. The patient took the initiative to go to the hospital because his leg was painful and was advised to do an MRI, the results of the MRI examination stated that the patient had an ACL and Meniscus rupture. The patient has undergone ACL reconstruction surgery and partial lateral meniscectomy on July 20, 2022, the patient has been doing physiotherapy since the first postoperative day until now entering the 10th week, the patient still feels something is stuck in the knee, and feels that left leg is stiff and weak when moved. Conclusion: There is an increase in ROM measurement results, muscle strength, segment circumference, hamstring and trunk flexibility, functional knee, and decreased pain scale. It is hoped that this case can be used as a reference for providing exercise interventions in patients with ACL postoperative conditions, especially phase III with other comorbidities.